Estrategias de investigación comunicacional en perspectiva de diseño e implementación de un departamento de comunicación en el Centro Comercial Municipal las Mercedes del cantón El Guabo periodo 2012- 2013. - Ordoñez Ordoñez, Esther Eliana (2015)
This research is, COMMUNICATIONAL RESEARCH STRATEGIES IN PERSPECTIVE OF DESIGN AND IMPLEMENTATION OF A DEPARTMENT OF COMMUNICATION IN THE MALL THE MERCEDES OF MUNICIPAL CANTON GUABO PERIOD 2012- 2013, Which it has been a lack of management of a strategic communications plan for the design and organization of the Department of Communication.